Park za tantsuvashti mechki . Dancing Bear Park - Traikova, Eldora (Pro Film Productions ; Bulgarian National Film Centre ; Jan Vrijman Fund, 2004)
Bulgaria is the last country in Europe where not long ago, dancing bears could be spotted in the streets, led on chains by bear-keeping gypsies. With the financial help from the Brigitte Bardot foundation, the world's largest and most sophisticated Dancing Bear Park was built near the small mountain town of Belitsa, and the surviving animals were resettled there. The film tells the story of the bears and of the people – the former bear-keepers who have been left without their livelihood, and the local impoverished population, who say with envy: "In Belitsa bears live better than people!" The goal-oriented NGO leader buys off the bears from their keepers for what they consider small money. He is happy with his state-of-art bear park explaining the initial skepticism of locals. Yet the ex-owners are not only shedding tears of separation, but have serious insecurities about the future income.